High Wage Workers and High Wage Peers - Michele Battisti (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2013)
This paper investigates the effect of co-worker characteristics on wages, measured by the average person effect of coworkers in a wage regression. The effect of interest is identified from within-firm changes in workforce composition, controlling for personeffects, firm effects, and sector-specific time trends. My estimates are based on a linked employer employee dataset for the population of workers and firms of the Italian regionof Veneto for years 19822001. I find that a 10 percent increase in the average labour market value of co-workers' skills is associated with a 3.6 percent wage premium. I alsofind that around one fourth of the wage variation previously explained by unobserved firm heterogeneity is actually due to variation in co-worker skills, and that between 10 and 15 percent of the immigrant wage gap can be explained by differences in coworkercharacteristics.
Keywords: J31; J79; 330; Spillover effects; linked employer-employee dataset; skill segregation